Ações afirmativas no mercado de trabalho: um estudo sobre a concretização do direito fundamental ao trabalho no Brasil - Araújo, Elizabeth Alice Barbosa Silva de (2012)
This dissertation studies the realization of the fundamental right to work in Brazil through affirmative action. We present the topics of the theory of fundamental rights that justify the use of affirmative action at work as an instrument guaranteeing the substantive equality, and the mechanisms used to solve the conflict between constitutional principles of the social value of work and free enterprise. The research looks at the time of access to formal job, when, on one side stands the freedom to hire of the employer and on the other the right to equal opportunities for workers. It is introduced the history and concept of affirmative action, and checked the various justifications for its implementation, for, in order to introduce the specificity of its action on the Brazilian labor market. Human labor as a way of survival and cultural as well as social expression, is analyzed within the contemporary context, with emphasis on the social impacts of public policies on access to employment. The reality of discrimination is brought by statistics that show negative form thereof to certain groups of workers. Were chosen for evaluation of the relevance and scope, the two cases in which the Brazilian legislator elected compulsory recruitment quotas in the private sector as an instrument to fight discrimination: Article 93 of Law 8.213 as of July 24, 1991, which brings shares reserved for people with disabilities, and Articles 428 and following of the Consolidation of Labor Laws, relating to law of learning. For this assessment we made a preliminary approach on the criterion of efficacy, present in the general theory of law in their legal, logistical and social aspects. Finally, field research was conducted to determine the degree of social efficiency of these affirmative action in employment, measured through the interpretation of data collected on a questionnaire.